PEMANFAATAN LIMBAH BIJI DURIAN (Durio zibethinus) SEBAGAI SUBSTRAT ALTERNATIF PEMBUATAN TEMPE BIJI DURIAN DENGAN PERBANDINGAN KADAR RAGI DAN LAMA FERMENTASI - Khisbul Maulana El Romadhon; Deny Utomo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Tempe is a food product that is very popular in Indonesia which is processed with a fermentation process in a certain time using Rhizopus oligosporus mushrooms. The waste of durian seeds (Durio zibethinus) into an alternative substrate in the manufacture of tempe is an innovation material in making tempeh. Here we have conducted research on durian seed tempeh, with the variables studied: yeast levels and fermentation duration. Based on the results of chemical analysis and organoleptic tests obtained by durian seed tempeh by consumers, namely the F3R3 treatment (danger of 2% yeast content and 72 hours of fermentation time: 100 g of durian seeds).